Native Americans in Sherman Alexie´s Work - Jirsová, Michaela (Univerzita Pardubice, 2012)
The aim of this paper is to analyse two important novels Indian Killer and The Absolutely True Diary of a Part-Time Indian by Sherman Alexie. These works describe how difficult it has been for Native Americans to assimilate into mainstream American culture in light of the past hardships they have suffered and current difficult living conditions either on or off the reservation. The point of this analysis is to show that Native Americans had to overcome many insurmountable obstacles after European settlers had arrived in Northern America. Despite this backdrop of a painstakingly torrid journey, some Native Americans have successfully adapted into mainstream American culture and became an integral part of a contemporary American society. To provide background for the study of Native Americans living in the U.S., historical-cultural context is explained.
Američané indiánského původu v díle Shermana Alexie
Keywords: Američané indiánského původu; rezervace; chudoba; asimilace; Absolutely True Diary of a Part-Time Indian; Indian Killer; Alexie, Sherman; identita; urbanizace; Native Americans; reservations; poverty; assimilation; identity; urbanization